TNF-alpha increases angiogenic potential in a co-culture system of dental pulp cells and endothelial cells - Li AN; Shuai SHEN; Luyao WANG; Yong LI; Sidra FAHIM; Yumei NIU; Shuang PAN (Sociedade Brasileira de Pesquisa Odontológica, 2019)
Abstract We recently demonstrated that a co-culture system of human umbilical vein endothelial cells (HUVECs) and human dental pulp stem cells (hDPSCs) could enhance angiogenesis ability in vitro. However, whether tumor necrosis factor α (TNF-α) could promote blood vessel formation during pulp regeneration remained unknown. The aim of this study was to investigate the effects of TNF-α on the formation of endothelial tubules and vascular networks in a co-culture system of hDPSCs and HUVECs. hDPSCs were co-cultured with HUVECs at a ratio of 1:5. The Matrigel assay was performed to detect the total tubule branching lengths and numbers of branches, and the Cell-Counting Kit 8 assay was performed to examine the effect of TNF-α on cell proliferation. Real-time polymerase chain reactions and western blot were used to detect vascular endothelial growth factor (VEGF) mRNA and protein expression. The Matrigel assay showed significantly greater total branching lengths and numbers of branches formed in the experimental groups treated with different concentrations of TNF-α compared with the control group. The decomposition times of the tubule structures were also significantly prolonged (P < 0.05). Treatment with 50 ng/ml TNF-α did not significantly change the proliferation of co-cultured cells, but it significantly increased the VEGF mRNA and protein expression levels (p < 0.05). In addition, the migration abilities of HUVECs and hDPSCs increased after co-culture with TNF-α (p < 0.05). TNF-α enhanced angiogenic ability in vitro in the co-culture system of hDPSCs and HUVECs.